Tata Ruang Arsip di Kantor Perpustakaan, Arsip dan Dokumentasi Kota Padang Panjang - Surya, Radifan; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
The purpose of this paper is: 1) to describe how the spatial planning in the Office of Libraries, Archives and Documentation of Padang Panjang; 2) to describe the obstacles encountered in the Office of the Spatial Archive and Documentation Library Archives Town Padang Panjang in an archive lay out; 3) to describe what efforts have been made Office of Library Archives and Documentation of Padang length in spatial archives. The data source of this study is that oral sources told directly by informants as the original speakers. Data were collected through observation and interviews with archivists at the Office of Libraries, Archives and Documentation of Padang Panjang. Keywords: spatial planning; archive